Charting New Paths in Critical Social Inquiry (Critical Journal of Social Sciences, 2026)
Welcome to the inaugural issue of the Critical Journal of Social Sciences, a new interdisciplinary platform dedicated to fostering rigorous, reflective, and critical scholarship across the social sciences. The world we live in is increasingly complex, uncertain, and contested — shaped by rapid political, economic, cultural, and technological transformations that cut across traditional disciplinary boundaries. Now more than ever, we require spaces where diverse forms of knowledge can come into conversation with one another, allowing scholars to reflect collectively on pressing social questions.